The Impact of Wind Accretion in Evolving Symbiotic Systems - Raul F. Maldonado; Jesús A. Toalá; Janis B. Rodríguez-González; Emilio Tejeda (The Astrophysical Journal)
We investigate the impact of geometric corrections to the Bondi–Hoyle–Lyttleton (BHL) accretion scheme applied to evolving symbiotic systems. We model systems where 0.7 and 1 M _⊙ white dwarfs (WDs) accrete material from solar-like stars with initial masses of 1, 2, and 3 M _⊙ . The primary star is evolved using the MESA stellar evolution code, while the orbital dynamics of the system are calculated using REBOUND. The analysis focuses on systems evolving through the red giant branch and the thermally pulsating asymptotic giant branch phases that do not experience a wind Roche lobe overflow phase. We compare three scenarios: no accretion, standard BHL accretion, and the improved wind accretion. The choice of accretion prescription critically influences the evolution of symbiotic systems. Simulations using the modified model did not reach the Chandrasekhar limit, suggesting that Type Ia supernova progenitors require accretors originating from ultramassive WDs. In contrast, the standard BHL model predicts WD growth to this limit in compact systems. This discrepancy suggests that population synthesis studies adopting the traditional BHL approach may yield inaccurate results. The revised model successfully reproduces the accretion properties of observed symbiotic systems and predicts transitions between different accretion regimes driven by donor mass-loss variability. These results emphasize the need for updated wind accretion models to accurately describe the evolution of symbiotic binaries.